Effect of Probiotics on the Length and Weight of Broilers Small Intestine (UNIVERSITAS ISLAM LAMONGAN, 2024)
The increasing need for chicken meat consumption every year makes farmers have to optimize the target of broiler production performance. One solution to maximize production targets is to provide probiotics. Probiotics are live microorganisms that function to increase the effectiveness of the gastrointestinal tract. The media used in making probiotics is prebiotics in the form of milk powder waste with kefir grain starter. In probiotic solutions there are several types of bacteria such as Lactobacillus, Bacillus sp. The purpose of this study was to increase the intestinal length of broiler chickens by probiotic supplementation in finisher phase broiler chickens. The research employed a Group Randomized Design (RAK) comprising 4 treatments and 5 repeats, namely P0 (Without probiotics), P1 (3% probiotics), P2 (5% probiotics) and P3 (7%) implementation of probiotics in broiler chicken drinking water given every afternoon to morning, using One Way ANOVA statistical test parameters with Duncan follow-up tests. Based on the results of P0, P1, P2 and P3 studies that have been carried out, the best probiotic dose research results were obtained at P3 (7% probiotics) with duodenal length worth 50.4 cm, jejenum 86.2 cm and ileum worth 52 cm. The weight of duodenum is worth 29.7 grams, jejenum is worth 30.4 grams and ileum is 30.1 grams.